MULTI-OBJECTIVE VEHICLE ROUTING PROBLEM WITH TIMES WINDOWS DENGAN PENDEKATAN GOAL PROGRAMMING UNTUK MENYELESAIKAN MASALAH OPTIMISASI RUTE PERJALANAN BUS PARIWISATA - Manaqib, Muhammad; Pantoro, Renova Dedi (IAIN Batusangkar, 2017)
Determining the route of the tourism bus to visit some tourism object not only to minimaze the distance, but also there are another purpose, such as minimization cost, maximizing tourism object, minimizing trip time, and maximizing the visit time in the tourism object. But, determining the route we should notice the open hours of the tourism object and operational hours for the tourism bus. The matter of determining the rute that involve some purpuse and considering the visit hours in the math is known as multi-objective vehicle routing problem with times windows. Goal programming is one of technique to solve the model with the multi-objective function and assist to find an optimal solution form several an compatible purpose. The purpose of goal programming is to minimize the total of deviation of all the purpose. Based on the case, goal programming will be apply the multi-objective vehicle routing problem with times windows which has been finised with goal programming approachment. Then, from the model it applied for the trip route of tourism agen Purpledia Pictures T&T in Bali island. The completion with LINGO, give an optimal route solution of the tourism bus, as many as three route with total cost IDR 1.269.700,00, as 25 tourism object which has been visited from 49 tourism place, the tour time 14.1 hours in 3 days and the total time to visited of tourism object 27 hours in 3 days.